La construcción de los imaginarios en los cuentos orales del cantón Chunchi - Carreño Rodríguez, Johanna Brigitte (2024)
This research analyzes the creation of imaginaries in the oral tales of the Chunchi canton based on two oral tales collected from two residents of the Compud parish. Customs have been preserved and transmitted through oral tradition; however, nowadays, oral narratives have lost value and, as a result, have gradually disappeared. In order to carry out this research, backgrounds from similar studies were used, and a detailed theoretical framework on orality, imagination, images, image-makers, values, culture, and tradition was developed. This research has a qualitative, documentary-descriptive approach, with the main interest of this research being to identify the relationship between imaginaries, images, and image-makers in oral tales and what types of imaginaries exist. The research presents the value of social and religious imaginaries. For this analysis, we work with the help of a table based on Pelegrín, Badillo, and the Royal Spanish Academy theories. With the collaboration of two residents of the Compud parish in the Chunchi canton, two local oral tales were collected and transcribed for analysis, where imaginary forms were identified in specific fragments and interpreted. A research instrument was applied, part of the qualitative paradigm that revealed a lack of knowledge about traditional oral tales among most residents. Finally, it was possible to identify the types of imaginary forms in the tales, highlighting that they represent the community's identity, customs, beliefs, and traditions.